The whale [videorecording (Blu-Ray)] - Hunter, Samuel D.; Fraser, Brendan, 1968-; Sink, Sadie; Chau, Hong, 1979-; Simpkins, Ty; Morton, Samantha; Hunter, Samuel D. (Lionsgate, 2023)
A reclusive English teacher suffering from severe obesity attempts to reconnect with his estranged teenage daughter for one last chance at redemption.